PERANCANGAN BUSINESS MODEL LEAN CANVAS BERBASIS USAH RINTISAN (STARTUP) DI LIKUPANG SEBAGAI DESTINASI PARIWISATA SUPER PRIORITAS DI KABUPATEN MINAHASA UATARA - Agustinus Walansendouw; Bet El S. Lagarense; Meyske Wisye Manopo; Geofane Daud; Faily Sitata (Jurnal Ilmu Pariwisata, 2022)
A startup is an organization designed to find a new business model to earn more profits. However few startups have failed. According to Forbes.com site records, 90% of startups made in the world failed. There are many reasons why startups failed including predicting market needs, internal conflicts, running out of funds, and the team experienced disharmony and poor corporate patterns. A startup in this research is an organization that is designed to create a product or service under uncertain conditions. A successful startup is not derived from successful predecessors but can be learned and can be taught. This research aims to design a lean canvas business model that is suitable for MSMEs in Likupang, North Minahasa Regency. Besides to determine the Canvas Business map model for culinary SMEs and handicraft SMEs. Finally to propose an inversion of the use of the Canvas Business Model for Culinary SMEs and Craft SMEs as one of the pioneers in providing food and beverages as well as and souvenirs which offers convenience and marketing strategies. It is suggested that using Lean Canvas in determining ideas and documentation in stepping and deciding targets. This will also make MSMEs and customers from the MSME market geting lots of convenience and savinh more costs. The application of business models such as Business Model Canvas and Lean Canvas in Culinary and Craft UMKM startups aims to represent a company that can operate and describe a relationship from technology developers to generate economic value. Lean Canvas focuses more on problems and as a tool for measuring and documenting business models and progress in the business.